TRENDS OF CHANGES IN THE SELECTION SYSTEMS OF ATHLETES-CANDIDATES TO UKRAINIAN NATIONAL TEAM FOR PARTICIPATION IN THE OLYMPIC GAMES (USING THE EXAMPLE OF MARTIAL ARTS) (Physical Culture and Sport: Scientific Perspective, 2022)
The article analyzes the peculiarities of the selection systems of athletes-candidates to the national team of Ukraine for participation in the Olympic Games (using the example of martial arts). The topicality of the work is connected with the need to develop and implement an effective model of Olympic training in martial arts taking into account the modern trends of their development. This would allow to compete decently with the world top athletes on the international arena. The purpose of the study was to determine the features of current systems of selecting athletes-candidates for the national team of Ukraine for participation in the Olympics (on the example of martial arts) and their comparison with the previous Olympic cycle.Research methods. Theoretical analysis, generalization of data from literature and Internet, documentary method were used to identify the development trends of modern Olympic martial arts. They also allowed and analyze the selection systems which determine the inclusion of Ukrainian athletes in the starting lineup of participants at the Olympic Games in modern sports martial arts (fencing, boxing, freestyle and Greco-Roman wrestling, judo, taekwondo).The results. It was established that the requirements presented in the systems for selecting athletes-candidates for the Ukrainian national teams in various martial arts are almost similar. In most documents, the selection includes analysis of the athletes' performance dynamics at national and international events, rivalry and the results of personal matches with the main opponents who have obtained Olympic quota places. The main trends and changes in the selection systems in Olympic martial arts are the following: improvement of formation of national ranking lists, taking into account the modern requirements of anti-doping laws, athlete’s potential not only to win medals at the Olympic Games, but also to support other team members during the Olympic qualification period.
Keywords: athletes; selection; Olympic license; stages; national team